CO0004 OLDER AGE, CARDIOVASCULAR COMORBIDITY AND GLUCOCORTICOSTEROIDS ARE RISK FACTORS FOR COVID-19 HOSPITALISATION IN PATIENTS WITH INFLAMMATORY RHEUMATIC DISEASES: FIRST RESULTS OF THE GERMAN COVID-19-IRD REGISTRY. (13th June 2020) - Regierer, A.; Hasseli, R.; Hoyer, B.; Krause, A.; Lorenz, H. M.; Pfeil, A.; Richter, J.; Schmeiser, T.; Specker, C.; Strangfeld, A.; Voll, R.; Schulze-Koops, H.; et al.
Abstract : Background: Patients with inflammatory rheumatic diseases (IRD) and infection with SARS-CoV-2 may be at risk to develop a severe course of COVID-19. To gather knowledge about SARS-CoV-2 infections in IRD patients, a national registry was established to elucidate IRD specific profiles of COVID-19. Objectives: To identify risk factors for hospitalisation. Methods: Patients from the German registry on SARS-CoV-2 infection in IRD were analysed. Patients are enrolled with a pre-existing IRD and a positive lab-result for a SARS-CoV-2 infection. The main outcome parameter was hospitalisation versus non-hospitalisation. Multivariable logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (CI). Covariates included in the model were age group, gender, key comorbidities (cardiovascular, lung diseases, chronic renal insufficiency), prior and/or current use of glucocorticosteroids (GC) or NSAIDs and remission. Results: Until May 17th, 2020, data from 192 IRD patients with SARS-CoV-2 infection were reported (67 males; 124 females; 1 diverse). 64 patients were hospitalised, 21 patients were ventilated non-invasively/invasively and 15 patients died. Baseline characteristics are shown in table 1, stratified into the patient groups non-hospitalisation, hospitalisation without ventilation, and hospitalisation with ventilation. Non-hospitalised patients were younger, had less comorbidities and were less often treated with GC. In the group of hospitalised patients compared to non-hospitalised patients more patients were male (42% vs 32% male) with an even higher proportion in the ventilated patient group (57% male). In the multivariable logistic regression model, age>65 years (OR 5.1; 95%CI 2.3-11.4), cardiovascular comorbidity (OR 2.3; 95%CI 1.0-5.0), and prior and/or current treatment with GC (OR 2.6; 95%CI 1.2-5.4) were independently associated with hospitalisation. Conclusion: As has been described for COVID-19 in general, also in IRD male gender may be associated with a more severe course of the infection as the descriptive analysis of data shows. Risk factors for SARS-CoV-2 infection-dependent hospitalisation in IRD patients include age (>65 years), cardiovascular comorbidities, and prior and/or current treatment with GC. Disclosure of Interests: Anne Regierer Speakers bureau: Novartis, Celgene, Janssen-Cilag, Rebecca Hasseli Grant/research support from: Pfizer, Consultant of: Pfizer, Gilead, Novartis, Celgene, Abbvie, Medac, Bimba Hoyer: None declared, Andreas Krause: None declared, Hanns-Martin Lorenz Grant/research support from: Consultancy and/or speaker fees and/or travel reimbursements: Abbvie, MSD, BMS, Pfizer, Celgene, Medac, GSK, Roche, Chugai, Novartis, UCB, Janssen-Cilag, Astra-Zeneca, Lilly. Scientific support and/or educational seminars and/or clinical studies: Abbvie, MSD, BMS, Pfizer, Celgene, Medac, GSK, Roche, Chugai, Novartis, UCB, Janssen-Cilag, Astra-Zeneca, Lilly, Baxter, SOBI, Biogen, Actelion, Bayer Vital, Shire, Octapharm, Sanofi, Hexal, Mundipharm, Thermo Fisher., Consultant of: see above, Alexander Pfeil Grant/research support from: This study Investigator Initiated Study "Automatic assessment of joint space narrowing in rheumatoid arthritis based on the Post-hoc analysis" (number: IIS-2016-110818) is a part of the of the Investigator Initiated Study "The quantification of inflammatory related periarticular bone loss in certolizumab pegol treated patients with rheumatoid arthritis" (number: IIS-2014-101458) which is supported by UCB Pharma GmbH, Monheim, Germany., Jutta Richter Grant/research support from: Grant/research support from: GlaxoSmithKline and UCB Pharma for performing the LuLa-study., Tim Schmeiser Speakers bureau: Actelion, UCB, Pfizer, Christof Specker Consultant of: Abbvie, Boehringer Ingelheim, Chugai, Lilly, Novartis, Sobi, UCB, Celgene, Janssen-Cilag, MSD, Pfizer, Roche, UCB, Toshiba, Anja Strangfeld Speakers bureau: AbbVie, BMS, Pfizer, Roche, Sanofi-Aventis, Reinhard Voll: None declared, Hendrik Schulze-Koops: None declared, Ulf Müller-Ladner Speakers bureau: Biogen